Benzophenone vs. Copper/Benzophenone in Light‐Promoted Atom Transfer Radical Additions (ATRAs): Highly Effective Iodoperfluoroalkylation of Alkenes/Alkynes and Mechanistic Studies. Issue 18 (31st August 2016) - Beniazza, Redouane; Atkinson, Rachel; Absalon, Christelle; Castet, Frédéric; Denisov, Sergey A.; McClenaghan, Nathan D.; Lastécouères, Dominique; Vincent, Jean‐Marc
Abstract: Iodoperfluooralkylation of terminal alkenes and alkynes is effectively photo‐promoted by benzophenone2 (BP) or the photoreducible copper(II) complex1 . In particular, BP at 1 mol% in methanol upon 365 nm irradiation with a low‐pressure mercury lamp (type TLC=thin layer chromatography, 6 W) results in a fast reaction with excellent reaction yields. Complex1 and BP2 exhibited very similar reactivity, suggesting that the reactions involving1 are likely to be governed by the benzophenone photoactivation processes, rather than copper(I)/(II) redox processes. Mechanistic investigations using transient absorption spectroscopy revealed that a deactivation pathway of the benzophenone triplet ( 3 BP*) is via its reaction with the methanol solvent. We propose that the generated radicals, in particular . CH2 OH, play a key role in the initiation step forming Rf . by reacting with Rf I, Rf . then entering a radical chain cycle. 1 H NMR studies provided evidence that a substantial amount (∼7% NMR yield) of the hemiacetal CH3 OCH2 OH is formed, i.e., the possible by‐product of the reaction between . CH2 OH and Rf I. Finally, DFT calculations indicate that a triplet‐triplet energy transfer (TTET) process from 3 BP* to perfluorooctyl iodide (C8 F17 I) is unlikely or should be rather slow under the reaction conditions, consistent with the transient absorption studies. Abstract :